2022
DOI: 10.1158/1078-0432.ccr-22-1366
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and Future Implications of VEGF/VEGFR in Cancer Therapy

Abstract: Angiogenesis, the sprouting of new blood vessels from existing vessels, is one of six known mechanisms employed by solid tumors to recruit blood vessels necessary for their initiation, growth, and metastatic spread. The vascular network within the tumor facilitates the transport of nutrients, oxygen, and immune cells and is regulated by pro- and anti-angiogenic factors. Nearly four decades ago, vascular endothelial growth factor (VEGF) was identified as a critical factor promoting vascular permeability and ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(79 citation statements)
references
References 155 publications
0
79
0
Order By: Relevance
“…Vascular endothelial growth factor (VEGF), also known as a vascular permeability factor, is another important protein for regulating vascular endothelium. It not only induces angiogenesis but also mediates the disruption of the vascular barrier, resulting in vascular leakage 27 . VEGF receptor-2 (VEGFR-2) phosphorylates tyrosine at the Y658 and Y731 sites of VE-cadherin by inducing SRC family kinases, leading to destabilization of adherens junctions and increased endothelial cell permeability 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF), also known as a vascular permeability factor, is another important protein for regulating vascular endothelium. It not only induces angiogenesis but also mediates the disruption of the vascular barrier, resulting in vascular leakage 27 . VEGF receptor-2 (VEGFR-2) phosphorylates tyrosine at the Y658 and Y731 sites of VE-cadherin by inducing SRC family kinases, leading to destabilization of adherens junctions and increased endothelial cell permeability 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF‐C and D normally regulate lymphangiogenesis, whereas VEGF‐A, B, and PlGF primarily induce angiogenesis. Different biological reactions are triggered when VEGF‐A, B, Placental Growth Factor (PlGF), and D are bound to VEGFR‐2, VEGFR‐1, and VEGFR‐3, respectively 75 . Tumor angiogenesis and proliferation increase when VEGFs activate the intrinsic MEK/ERK/RAS/Raf, PKC/PLC, and AKT/PI3K signaling pathways.…”
Section: Tissue‐based Biomarkersmentioning
confidence: 99%
“…Different biological reactions are triggered when VEGF-A, B, Placental Growth Factor (PlGF), and D are bound to VEGFR-2, VEGFR-1, and VEGFR-3, respectively. 75 Tumor angiogenesis and proliferation increase when VEGFs activate the intrinsic MEK/ERK/RAS/Raf, PKC/PLC, and AKT/ PI3K signaling pathways. Among these, the VEGF-A receptors VEGFR-1 and VEGFR-2 are considered attractive targets for cancer treatment in therapeutic settings.…”
Section: Vegfmentioning
confidence: 99%
“…These drugs were originally designed to "starve the tumor". However, in clinical studies, it has been found that they temporarily "normalize" tumor blood vessels [8], and increase lymphocyte infiltration and T-cell activation [9]. In addition, vascular normalization can reduce the expansion of Myeloid-Derived Suppressor Cells (MDSCs) and the proliferation and differentiation of regulatory T cells (Treg) [10], eventually leading to the transformation of an immunosuppressive state into an immune-promoting state.…”
Section: Discovery Of Anti-angiogenic Drugsmentioning
confidence: 99%